High-capacity water sorbent cycles without hysteresis under dry conditions - Julius Oppenheim; Zhentao Yang; Bhavish Dinakar; Mircea Dincă (Nature Communications)
Abstract Sorbents capable of cycling water vapor under dry conditions are critical for applications such as atmospheric water harvesting, desiccation, and heat pumps; however, few existing sorbents demonstrate both hysteresis-free behavior and cycling stability. Here we show that post-synthetic exchange with lithium, sodium, potassium, magnesium, and tetramethylammonium in the metal-organic framework (MOF) SU-102 ([(CH3)2NH2]2[Zr(HL)2]; H4L = ellagic acid) enables high-capacity water sorption under low humidity ranging from 11.1% to 4.3%. The champion material, Mg-SU-102, exhibits sharp water uptake at 4.3% RH, reaches a high maximum gravimetric capacity of 0.41 g/g (with 0.29 g/g at 15% RH), and displays minimal capacity loss over 500 adsorption-desorption cycles, with essentially no hysteresis. We use vibrational Stark spectroscopy to probe the local electric field environment within each ion-exchanged material and show that the trend in relative humidity follows a Hofmeister-type series in which the cation affects the ability for water to solvate the framework pores. We find strong deviation from this trend for the tetramethylammonium material, as the larger cation does not undergo capillary condensation sorption, suggesting that fine control over pore functionality is necessary. Establishing a correlation between water sorption and a Hofmeister-type series provides foundational principles for the design of porous ionic sorbents.